“Germanophilism” of Bishop Dimitri (Abashidze) during the First World War: Bishop’s Answer to “The German Question” - V. V. Kalinovsky (Научный диалог)
The plot, connected with attacks on the head of the Taurida diocese Dimitri (Abashidze), accused of Germanophilism during the First World War is examined in the article. These events are inscribed in the context of the aggravation of the national question that happened in the wake of the military confrontation between the Russian Empire and Germany. The relevance of this study is due to the insufficient elaboration of the issue of the involvement of the Orthodox clergy in resolving interethnic relations, as well as the participation of the clergy in the Russian nationalist movement. The novelty of the research lies in the introduction of a new corpus of sources into the scientific circulation, which makes it possible to consistently trace how the solution of the regional conflict on ethnic grounds, due to the attention of the capital’s newspapers, reached the state level and was used in the political struggle. It is noted that the appeal of Dimitri (Abashidze) to the priests was the reason for accusing the hierarch of Germanophilism, in which the «Vechernee Vremya» newspaper was most zealous. It is shown that priests and public figures spoke in defense of the bishop. It is proved that the attacks on the Tauride bishop contributed to the intensification of his activities in the right political camp.